2016
DOI: 10.1007/s10495-016-1236-3
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the relationship between macroautophagy and mitochondrial ROS in cancer therapy

Abstract: Macroautophagy (Autophagy), an evolutionarily conserved cellular self-digesting process implicated in various physiological and pathological processes, is activated by different stimuli including oxidative stress. Reactive oxygen species (ROS) are involved in autophagy modulation through multiple signaling pathways and transcription regulators. Accumulating data support both a positive and negative role of ROS-modulated autophagy in cancer. As a tumor suppressive mechanism, autophagy induces autophagic cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 146 publications
0
26
0
Order By: Relevance
“…The activation of autophagy (often mediated by mitochondrial ROS [48]) is necessary to degrade misfolded or damaged cell components, including mitochondria, thus promoting cancer cell survival. However, under extreme conditions, it can act as programmed cell death mechanism type II [49].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of autophagy (often mediated by mitochondrial ROS [48]) is necessary to degrade misfolded or damaged cell components, including mitochondria, thus promoting cancer cell survival. However, under extreme conditions, it can act as programmed cell death mechanism type II [49].…”
Section: Discussionmentioning
confidence: 99%
“…During the initiation of apoptosis, an abnormal increase in ROS occurs, which is an important stimulus for mitochondrial apoptosis (35). It has been demonstrated that a number of drugs induce apoptosis of cancer cells by increasing ROS levels (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…ROS have multifaceted effects, and the function of ROS is determined by the redox state (Zhao et al, 2016). Oxidative stress is induced when ROS are produced in excess of the capacity of the antioxidant system to efficiently counteract their actions, resulting in cytotoxic effects and enhancing periodontal destruction (Nibali and Donos, 2013).…”
Section: Ros In Periodontitismentioning
confidence: 99%
“…Studies suggest that ROS influence autophagy and that autophagy reciprocally regulates ROS (He Y. et al, 2017; Wang et al, 2017). The most typical example of their interaction has been elucidated in cancer development (Zhao et al, 2016). Autophagy consists of five sequential steps: induction, elongation, maturation, transport to lysosomes, and degradation (Levine and Kroemer, 2008).…”
Section: Introductionmentioning
confidence: 99%